Malawi stories of change in nutrition: Evidence review - Roschnik, Natalie; Northcote, Callum; Chalemera, Jacqueline; Nowa, Mphatso; Lupafaya, Phindile; Bhaiji, Rashida; Museka Saidi, Tendai; Mhango, Brian (Institute of Development Studies, 2022)
A review of evidence was conducted to understand the trends and determinants of malnutrition and identify interventions and programmes that improved maternal and child nutrition in Malawi. While children are less malnourished than two decades ago, one in three children remains stunted (37%) and 63% are anaemic. Children born from younger and less educated mothers, or from poorer rural households are more likely to be malnourished. One in ten children are born with a low birth weight (< 2.5kgs), with nearly half of them stunted by age two. The main causes of malnutrition include recurring sickness, poor infant and young child feeding and hygiene practices and low use of health and nutrition services, influenced by a wide range of factors, including food insecurity, poverty, gender inequality and food taboos. Programme evaluations and intervention trials have shown mixed results but overall highlight the need to address the multiple underlying drivers of malnutrition, rather than focus on one intervention.